An indepth analysis of social movement and democratic consolidation in Zimbabwe: the case of the tajamuka from 2016-2017 - Manyika, Charity (Midlands State University, 2019)
The research analysed the purpose of and effects of social movement in Zimbabwe through examining acts of activism by prominent movements such as Tajamuka. This research is important to both the government and citizens as social movements are a gravity which influences the governance of this country hence the phenomenon has to be extensively understood. Government policies disturb every citizen in Zimbabwe and the actions that are taken by people against the government will generally affect everyone indirectly or vice versa. It is the objective of the research to provide an understanding on where acts of activism stand within the legal framework of Zimbabwe. This will give vital information to the people who would wish to be heard but do not get the consequences of being involved in a social movement. Generally, the research provide an in-depth analysis of issues surrounding social movements in the country. The research shall proffer solutions to activists in social movement’s arena to achieve democratic consolidation. The government requires ways to engage with people who does not entail use of state security personnel and citizens who wish to be heard and require transformation through a peaceful manner. A quantitative approach was utilized to unearth the various factors surrounding this study. Data collection methods such as interviews, questionnaires and participant observation were used to bring out a balanced and well-articulated thesis. The research focus on various stakeholders in the social movement paradigm such as their leaders, government officials and citizens.